Prototyping wireless pulse oximeter - Ng, Kimberly Jin Jin (2014)
The demographic time bomb has been a major concern for many countries around the globe. Many lives were lost owing to the neglect of one’s health condition. This paper describes the incorporation of ZigBee protocol into medical devices such as Pulse Oximeter. The wireless operating system adopted in this project has a range of 10-75 m coverage to transmit blood oxygenation (SpO2), pulse rate (BPM) and perfusion index (PI) to a centralized computer system.